High-performance piezoelectric (K, Na, Li)(Nb, Ta, Sb)O3 single crystals by oxygen annealing. (15th April 2018) - Liu, Hairui; Veber, Philippe; Rödel, Jürgen; Rytz, Daniel; Fabritchnyi, Pavel B.; Afanasov, Mikhail I.; Patterson, Eric A.; Frömling, Till; Maglione, Mario; Koruza, Jurij
Abstract: Ferroelectric single crystals exhibit the largest known piezoelectric constants and therefore show high potential for application in electronic devices, including sensors, actuators, and transducers. Their large properties, however, can only be fully exploited if the behavior is not influenced by lattice defects, formed during high-temperature processing. Such defects can inhibit domain-wall movement, increase leakage currents, and are predominantly responsible for the poor performance of the emerging ferroelectric crystals. Here, an approach to considerably enhance the piezoelectric and ferroelectric properties of (K, Na, Li)(Nb, Ta, Sb)O3 crystals by oxygen annealing is investigated. As compared to the non-annealed crystals, polarization, strain, and piezoelectric constant of the annealed sample were enhanced by a factor of two, resulting in an outstanding room-temperature value of piezoelectric constant d 33 = 732 pC/N and a peak value of d 33 = 1431 pm/V at the orthorhombic-tetragonal transition. The behavior was analyzed using electromechanical measurements, Mössbauer spectroscopy, and impedance spectroscopy, revealing decreased concentrations of both oxygen vacancies and Sb 3+ ions after annealing. The findings indicate that the control of the defect chemistry enables these ferroelectric (K, Na)NbO3 -based single crystals to outperform their polycrystalline counterparts and reach the values of lead-containing compositions. Moreover, the present strategy enables further detailed studies of the inherent crystal anisotropy and the possibilities for domain engineering. Graphical abstract: Image 1